Perencanaan Strategis SI/TI di PT.Segoro Mas Solo menggunakan Metode Ward and Preppard - Ign Excel Ekaristi Verares (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Abstract In the business world, information systems are needed, especially for companies and agencies to develop their business. PT. Segoro Mas Solo is a company engaged in furniture. This company has implemented the development of information systems by implementing ERP to develop the company's business development, but the ERP here is not fully integrated, there are several sections in PT. Segoro Mas Solo, which is still not integrated with existing systems, such as warehouse information systems, which still apply Microsoft Excel as its information system. Therefore, it can be overcome by strategic planning of information systems using the Ward and Peppard method. Where in this method also uses the SWOT analysis method, Porter's Five Forces analysis, and McFarlan Strategic Grid. The final result expected from this research is a strategic proposal mapping of information systems at PT. Segoro Mas Solo, which in the future can be applied as a reference for developing the company's business and increasing the company's competitiveness.